Design and development of rotating-sleeve refrigerant compressor - Mohd. Yusof Taib (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2005